2013
DOI: 10.1016/j.jaci.2013.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Maternal asthma and microRNA regulation of soluble HLA-G in the airway

Abstract: Background We previously reported an interaction between maternal asthma and the child’s HLA-G genotype on the child’s subsequent risk for asthma. The implicated SNP at +3142 disrupted a target site for the microRNA (miR)-152 family. We hypothesized that the interaction effect may be mediated by these miRs Objective The objective of this study was to test this hypothesis in adults with asthma who are a subset of the same subjects who participated in our earlier family-based studies. Methods We measured sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 44 publications
5
36
0
3
Order By: Relevance
“…Our previous studies (3,5,9) demonstrated associations between HLA-G genetic variation and sHLA-G expression levels in AECs from individuals with asthma. Here we show for the first time that sHLA-G concentrations in the airway are inversely correlated with markers of airway inflammation: asthmatic subjects, regardless of disease severity, with higher concentrations of sHLA-G had lower levels of BAL eosinophils and lower FeNO, both consistent with the Th2-low endotype in asthma.…”
Section: To the Editormentioning
confidence: 92%
“…Our previous studies (3,5,9) demonstrated associations between HLA-G genetic variation and sHLA-G expression levels in AECs from individuals with asthma. Here we show for the first time that sHLA-G concentrations in the airway are inversely correlated with markers of airway inflammation: asthmatic subjects, regardless of disease severity, with higher concentrations of sHLA-G had lower levels of BAL eosinophils and lower FeNO, both consistent with the Th2-low endotype in asthma.…”
Section: To the Editormentioning
confidence: 92%
“…One hundred twenty-three adult subjects (76 with asthma, 47 without asthma) underwent bronchoscopy between March 2010 and March 2014 at the University of Chicago. Endobronchial brushings were obtained during bronchoscopy, as previously described (37). The asthmatic subjects had a current doctor's diagnosis of asthma, no conflicting pulmonary diagnoses, and were using asthma medications.…”
Section: Methodsmentioning
confidence: 99%
“…Our asthma clinical research program has been collecting lower airway samples from both carefully characterized asthma patients and from control subjects [18, 19]. To overcome previous sampling inconsistencies, we decided to elucidate and model the variability in the microbiome of different lung regions; specifically, the bronchial (endobronchial brushing, EB) and small (bronchoalveolar lavage, BAL) airways.…”
Section: Introductionmentioning
confidence: 99%